How does climate change affect combined sewer overflow in a system benefiting from rainwater harvesting systems?. (November 2016) - Tavakol-Davani, Hessam; Goharian, Erfan; Hansen, Carly H.; Tavakol-Davani, Hassan; Apul, Defne; Burian, Steven J.
Highlights: CSOs are one of the greatest challenges to meet sustainability standards. Climate change may cause 12–18% increase in CSOs characteristics in Toledo. Rainwater Harvesting (RWH) was able to mitigate the climate change impacts. RWH could supply indoor toilet flushing demands in buildings in Toledo. RWH indicated a satisfactory performance in the peak flow events. Abstract: Combined Sewer Overflow (CSO) infrastructure are conventionally designed based on historical climate data. Yet, variability in rainfall intensities and patterns caused by climate change have a significant impact on the performance of an urban drainage system. Although rainwater harvesting (RWH) is a potential solution to manage stormwater in urban areas, its benefits in mitigating the climate change impacts on combined sewer networks have not been assessed yet. Hence, the goal of the present study was set to evaluate the effectiveness of RWH in alleviating the potential impacts of climate change on CSOs. To do so, first, future rainfall was achieved through the Coupled Model Intercomparison Project Phase 5 (CMIP5) based on modified historical record. Then, rainfall-runoff modeling was employed using the U.S. EPA Stormwater management model (SWMM) to study the response of CSO outfalls to future rainfall. The study site was the combined sewer network of the City of Toledo, Ohio. Results showed that under the maximum impact scenario in the near future, climate change might cause up to approximately 12–18% increase in CSOs occurrence, volume and duration in Toledo. However, an RWH plan with the capacity of 0.76 m 3 (200 gal) implemented on half on the buildings throughout the area, appeared to be able to mitigate the potential future impacts, and showed a remarkable controlling performance in the peak flow periods. This plan also met toilet flushing demands. Therefore, RWH can be considered as a feasible solution to mitigate future climate change impacts on CSOs and supply water demands.